2012
DOI: 10.1371/journal.pone.0029371
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of B2 but Not B1a B Cells in BAFF Receptor-Deficient ApoE−/− Mice Attenuates Atherosclerosis by Potently Ameliorating Arterial Inflammation

Abstract: We have recently identified conventional B2 cells as atherogenic and B1a cells as atheroprotective in hypercholesterolemic ApoE−/− mice. Here, we examined the development of atherosclerosis in BAFF-R deficient ApoE−/− mice because B2 cells but not B1a cells are selectively depleted in BAFF-R deficient mice. We fed BAFF-R−/− ApoE−/− (BaffR.ApoE DKO) and BAFF-R+/+ApoE−/− (ApoE KO) mice a high fat diet (HFD) for 8-weeks. B2 cells were significantly reduced by 82%, 81%, 94%, 72% in blood, peritoneal fluid, spleen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 43 publications
(76 reference statements)
13
113
3
2
Order By: Relevance
“…Deletion of the BAFF receptor (BAFFR), necessary for B2 development, was also recently shown to be protective in at least two studies (968,1528). Like the anti-CD20 antibody infusion studies, BAFFR deficiency resulted in marked selective reduction of B2 cells with little effect on B1a cells.…”
Section: The Atherogenic Effect Of Igg Appears To Depend On the Targetmentioning
confidence: 99%
“…Deletion of the BAFF receptor (BAFFR), necessary for B2 development, was also recently shown to be protective in at least two studies (968,1528). Like the anti-CD20 antibody infusion studies, BAFFR deficiency resulted in marked selective reduction of B2 cells with little effect on B1a cells.…”
Section: The Atherogenic Effect Of Igg Appears To Depend On the Targetmentioning
confidence: 99%
“…On the other hand, use of anti-CD20 to deplete B-2 cells in mice, which spared B-1 cells in the peritoneum, reduced atherosclerosis, as well as activation and proliferation of DCs and CD4 + T cells, suggesting that B-2 cells were proatherogenic by several mechanisms (60,94). Furthermore B cell-activating factor receptor (BAFF-R) deficiency, which causes a reduction in B-2 but not B-1 cells, also reduced lesion development and macrophage and T cell infiltration (95,96). However, recent data demonstrated a role for the Id3-CCR6 pathway in mediating aortic B cell homing, and demonstrated that resident adventitial B cells mediated protection from early atherosclerosis in part through inhibiting intimal macrophage accumulation (97).…”
Section: B Cells and Ab Responses In Atherosclerosis B-1 Cells And Igmentioning
confidence: 99%
“…To date, it is generally accepted that (auto)antibody‐producing B1 B cells are atheroprotective26, 27 and this protective effect depends on IgM secretion,28 whereas conventional B2 B cells are generally considered proatherogenic 29. This proatherogenic phenotype in mice has mainly been attributed to the production of pathogenic IgG antibodies against oxidized low‐density lipoprotein (oxLDL) and the immune effector function of these B cells 27, 28, 30, 31, 32, 33. In human atherosclerosis, however, there is conflicting evidence about the role of autoantibodies directed against oxLDL.…”
Section: Introductionmentioning
confidence: 99%